Gender Differences in Physical Fitness and Personal Ressilience in Vovational Students Indonesia - Sigit Susilo; Agung Yuda Aswara; Susilo Bekti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
Although it is often a topic of discussion, it turns out that there has been no in-depth research on physical fitness and personal resilience in Indonesia.This study poses a problem: does the physical fitness and personal resilience of vocational students in Indonesia meet the predetermined good criteria, compares the physical fitness and personal resilience of vocational students in Indonesia based on gender, and is there a relationship between physical fitness and personal resilience of vocational students in Indonesia? This study used data from the Center for Physical and Sports Literacy Studies, Master of Sports Education, IKIP Budi Utomo Malang. The population is infinite because the distribution of the questionnaire uses the snowball sampling technique. The total sample is 1713 vocational students in Indonesia, consisting of 872 male students and 825 female students.Data were analyzed with a single mean test with criteria, two different test means, and a correlation test. It was concluded that the physical fitness of vocational high school students, both male and female, in Indonesia did not meet the predetermined good criteria; there was no difference in the physical fitness of male and female vocational high school students in Indonesia. The personal resilience of vocational high school students, both male and female, and women in Indonesia have met the predetermined good criteria; there is no difference in the personal resilience of male and female vocational students in Indonesia; there is a relationship between physical fitness and the personal resilience of vocational students in Indonesia.